Topical Intranasal Lidocaine is not a Sphenopalatine Ganglion Block. Issue 4 (22nd December 2021) - Narouze, S.
Abstract : ( Reg Anesth Pain Med . 2021:46. PMID: 33323391) There is a complex network of nerves within the pterygopalatine fossa. The largest peripheral parasympathetic ganglion, located within the pterygopalatine fossa, is the sphenopalatine ganglion (SPG) which plays an important role in managing primary and secondary headache disorders. Recent interest exists in applying local anesthetics (LA) as an SPG block to manage headaches, especially postdural puncture headache management. This discourse reviews why intranasal LA application is not an acceptable and effective route for SPG block.